2015
DOI: 10.1039/c5ra13305j
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and optical properties of Fe doped crednerite CuMnO2

Abstract: A geometrically frustrated magnetic CuMnO 2 system has been investigated because of its rich magnetic properties. Neutron diffraction, synchrotron X-ray, magnetic, X-ray photoemission spectroscopy (XPS) and UV-Visible spectroscopy measurements have been carried out on CuMnO 2 and 5% Fe doped CuMnO 2 samples. Fe doping reduces the distortion. Moreover, Fe doping induces the ferromagnetic coupling between ab planes. The value of magnetization is increased with Fe doping but coercivity is decreased. These migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The results confirmed that the mixed Mn 3+ /Mn 4+ ions states existed in CuMn 1−x Cr x O 2 (0 ≤ x ≤ 0.8) samples, which indicated that the Jahn-Teller distortion effect occurred on the structure. 13 In fact, the Jahn-Teller distortion behavior was decreased with increasing x content.…”
Section: Xps Spectramentioning
confidence: 99%
See 3 more Smart Citations
“…The results confirmed that the mixed Mn 3+ /Mn 4+ ions states existed in CuMn 1−x Cr x O 2 (0 ≤ x ≤ 0.8) samples, which indicated that the Jahn-Teller distortion effect occurred on the structure. 13 In fact, the Jahn-Teller distortion behavior was decreased with increasing x content.…”
Section: Xps Spectramentioning
confidence: 99%
“…The distorted structure in turn caused lattice instability, which is a Jahn-Teller distortion called the Jahn-Teller effect. 12,13 The valence of Mn in the CuMnO 2 structure potentially displays M 3+ ions, while the existence of Mn 4+ ions in the nonstoichiometric Cu 1+x Mn 1−x O 2 structure displayed the formation of mixed Mn 3+ /Mn 4+ ions for stabling electrical neutrality in the structure. 14 The mixed-valent Mn 4+ /Mn 3+ state contributed to the Jahn-Teller effect following the Hund's rule, by coupling between the e g electrons on Mn 4+ ions and the t 2g core electrons on Mn 3+ ions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the etching of the film, this peak appears as a part of the shoulder at 531-532 eV. The spectra shoulders around 531 eV refer to excess oxygen (marked as O − ) [37]. The incorporated nitro (532.7 eV) [38] and hydroxyl (533 eV) [39] groups cause a shift in O1s and are responsible for the high-energy shoulder.…”
Section: Samples Comositionmentioning
confidence: 99%